Inklusi Keuangan Digital Bagi Petani Perempuan Di Wajo: Sebuah Studi Grounded Theory - Amin, Andi Mustika (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
The study examines how women farmers in Wajo are adopting digital financial services through a grounded theory approach, focusing on the social, moral, and structural dynamics that shape their financial inclusion practices. Data were collected over five months in 2023 through in-depth interviews, participant observations, and document analysis in three purposively selected villages and then deepened through theoretical sampling. The analysis resulted in four main categories-Instrumental Necessity, Mediated Trust, Moral-Economic Calculus, and Structural Gateways—that collectively build a core process titled “Relational Mediation of Digital Finance."The findings suggest that women's use of digital finance is not merely a technical or economic decision, but rather a social process mediated by family relationships, moral norms, and infrastructure readiness. Trusts are more transacted through intermediaries—children, young relatives, cooperative staff, or village agents-than through the digital platform itself. In addition, moral-economic considerations regarding reputation, religious duty, and social reciprocity were shown to moderate decisions to borrow or save digitally. Structural barriers such as network limitations, identity document mismatch, and application design also affect participation. The study affirms that financial inclusion interventions must be multidimensional-incorporating infrastructure strengthening, culturally contextual product design, and the use of local actors as digital brokers—to improve the acceptability and sustainability of digital financial services for women farmers in rural areas of Indonesia.